2023
DOI: 10.3390/ijerph20043041
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Meaning in Life and Depression among Chinese Junior High School Students: The Mediating and Moderating Effects of Cognitive Failures and Mindfulness

Abstract: In recent years, the incidence of depression among adolescents has been increasing yearly, and the severe damage of depression on adolescents’ physical and mental health development has caused extensive concern worldwide. Previous research on adults has confirmed that meaning in life is a crucial buffer factor for depression, and developing meaning in life is an essential task in adolescence. Moreover, prior researchers also pointed out that frequent cognitive failures can induce negative emotions in individua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…However, inconsistent results suggest that this association is not robust. For example, Li, Li et al (2007) found that PIU was positively correlated with parental emotional warmth, while other researchers reported opposite results ( Li et al, 2012 ; Zhang, Bai, Jiang, Yang, & Zhou, 2019 ). Similarly, inconsistent findings have been reported regarding the associations between behavioral/psychological control, dimensions of parenting style, and PIU.…”
Section: Introductionmentioning
confidence: 96%
“…However, inconsistent results suggest that this association is not robust. For example, Li, Li et al (2007) found that PIU was positively correlated with parental emotional warmth, while other researchers reported opposite results ( Li et al, 2012 ; Zhang, Bai, Jiang, Yang, & Zhou, 2019 ). Similarly, inconsistent findings have been reported regarding the associations between behavioral/psychological control, dimensions of parenting style, and PIU.…”
Section: Introductionmentioning
confidence: 96%
“…Negative coping strategies can aggravate the negative impact of the disease [7], leading to negative emotions in patients [8]. Mindfulness is focusing attention on the present and perceiving each moment of experience in a receptive and nonjudgmental manner [9], which can help patients maintain their attention and alertness to current events [10], freeing them from bad thinking patterns and negative emotions [11]. At present, it is generally believed that the core factors of mindfulness are "attention" and "open attitude".…”
Section: Introductionmentioning
confidence: 99%
“…This study highlighted the importance of considering individual differences in understanding cognitive failures (Markett et al, 2019). Li et al (2023) explored the mediating and moderating effects of cognitive failures and mindfulness in the relationship between meaning in life and depression among Chinese junior high school students. Their findings indicated that cognitive failures mediated the relationship between meaning in life and depression, suggesting that interventions aimed at reducing cognitive failures could mitigate depressive symptoms (Li et al, 2023).…”
Section: Introductionmentioning
confidence: 99%